Medir a Sociedade de Informação - Montargil, Filipe (2022)
Montargil, F., Fátima, B. D., Rodrigues, V., & Santos, V. (2019). Medir a Sociedade de Informação: Sistema para um painel online de utilizadores da Internet. In R. Goncalves, I. Pedrosa, M. P. Cota, & A. Rocha (Eds.), 2019 14th Iberian Conference on Information Systems and Technologies (CISTI): proceedings [8760838] (Iberian Conference on Information Systems and Technologies, CISTI; Vol. 2019-June). IEEE Computer Society. https://doi.org/10.23919/CISTI.2019.8760838